Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.22214/ijraset.2022.46864
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Hybrid Energy System (Solar-Wind) Supported with Battery Energy Storage

Abstract: The utilization of renewable energy is significantly important for the world because global energy consumption is increasing, while conventional energy sources are no longer sufficient to meet the energy demand, triggering energy crises. In recent years, the increasing prices of fossil fuels and concerns about the environmental consequences of greenhouse gas emissions have renewed the interest in the development of alternative energy resources. Renewable energy is now considered a more desirable source of fuel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…The development of hybrid renewable energy systems, combining solar and wind energy supported by battery storage technology, represents another innovative approach to overcoming the limitations posed by fluctuating renewable energy outputs. Srivastava (2022) focuses on the generation of hybrid solar-wind power plants, emphasizing the optimal contribution of renewable resources. This approach is seen as a promising solution to ensure stable operation of renewable energy systems across different geographical locations, further contributing to the diversification and resilience of the energy supply (Srivastava, 2022).…”
Section: Technological Innovations and Developments Advances In Renew...mentioning
confidence: 99%
See 1 more Smart Citation
“…The development of hybrid renewable energy systems, combining solar and wind energy supported by battery storage technology, represents another innovative approach to overcoming the limitations posed by fluctuating renewable energy outputs. Srivastava (2022) focuses on the generation of hybrid solar-wind power plants, emphasizing the optimal contribution of renewable resources. This approach is seen as a promising solution to ensure stable operation of renewable energy systems across different geographical locations, further contributing to the diversification and resilience of the energy supply (Srivastava, 2022).…”
Section: Technological Innovations and Developments Advances In Renew...mentioning
confidence: 99%
“…Srivastava (2022) focuses on the generation of hybrid solar-wind power plants, emphasizing the optimal contribution of renewable resources. This approach is seen as a promising solution to ensure stable operation of renewable energy systems across different geographical locations, further contributing to the diversification and resilience of the energy supply (Srivastava, 2022). Technological innovations and developments in renewable energy technologies, including advancements in solar power, wind energy, and battery storage, are crucial for achieving sustainable energy goals.…”
Section: Technological Innovations and Developments Advances In Renew...mentioning
confidence: 99%
“…Solar and wind resources could attain higher reliability levels by introducing energy storage, boosting the installation capacity (i.e., producing power in excess of annual demand), or pooling resources from adjacent locations. Srivastava [36] suggested that the most effective use of PV-WT technology was for off-grid services, which could reach remote areas without the need for costly electrical network expansion. As a result, standalone systems powered by renewable energy sources have gained popularity.…”
Section: Figure 1 Average Solar Radiationmentioning
confidence: 99%
“…This system is more reliable in remote rural areas because it is customizable according to the required load and cannot breakdown due to faults in other networks/units as it is off-grid. Its small setup has easy and low maintenance due to MPPT technology, providing optimal and regulated charging/supply [36].…”
Section: Figure 3 Nn Structurementioning
confidence: 99%